Review of the European genera of Eviphididae (Acari: Mesostigmata) and the species occurring in Slovakia - Mašán, Peter; Halliday, Bruce (Zootaxa, 2010)
The study presents a review of the European fauna of Eviphididae (Acari: Mesostigmata), based on over 4,000 specimens, including type specimens in the Berlese Acaroteca, Florence. The European fauna is shown to include 29 species in 16 genera. These genera are reviewed, and a key provided for their identification. The fauna of Slovakia includes 14 genera and 19 species. These species are reviewed, and keys are provided for their identification. The European fauna includes the genera Alliphis Halbert 1923, Alloseius Mašán & Halliday 2009a, Copriphis Berlese 1910, Crassicheles Karg 1963, Evimirus Karg 1963, Eviphis Berlese 1903, Halolaspis Mašán & Halliday 2009a, Neocrassicheles gen. nov., Pelethiphis Berlese 1911, Pseudoalliphis Mašán & Halliday 2009a, Rafaphis Skorupski & Błaszak 1997, Scamaphis Karg 1976, Scarabacariphis Mašán 1994a, Scarabaspis Womersley 1956, Thinoseius Halbert 1920 and Uroiphis Berlese 1903. All of these genera except Evimirus and Thinoseius occur in Slovakia. The genus Uroiphis Berlese 1903, with type species Uroiphis scabratus Berlese 1903 (= Eviphis holsaticus Willmann 1937), is considered to be a valid genus, and is removed from synonymy with Eviphis. The new taxa described here are Neocrassicheles gen. nov., with type species Neocrassicheles sternomus sp. nov., and Uroiphis montivagus sp. nov. The previously unknown adult female of Crassicheles striatus (Berlese 1903) and male of Uroiphis scabratus Berlese 1903 are described for the first time. The following new synonymies are proposed: Alliphis brevisternalis Ma & Wang 1998 and Alliphis yinchuanensis Gu & Bai 1997 are synonyms of Alliphis necrophilus Christie 1983; Alliphis hirschmanni Arutunian 1991 is a synonym of Alliphis scarabaeorum Ogandzhanyan 1969; Alliphis montanus Koroleva 1968, Alliphis rotundianalis Mašán 1994a and Scarabaspis altaicus Sklyar 1999 are synonyms of Alloseius pratensis (Karg 1965); Hypoaspis evansi Arutunian 1993 is a synonym of Scamaphis equestris (Berlese 1911); Iphidoides concentricus Oudemans 1904 is a synonym of Uroiphis striatus Berlese 1903; Eviphis holsaticus Willmann 1937 and Iphidosoma bennwili Schweizer 1961 are synonyms of Uroiphis scabratus Berlese 1903; Scarabacariphis grandisternalis Mašán 1994a is a synonym of Scarabacariphis ankavani (Arutunian 1992); Bactriphis Athias-Henriot 1980 is a synonym of Uroiphis Berlese 1903. The male and deutonymphal paratypes of Alliphis stenosternus Gu & Liu 1996 are misidentified specimens of Alloseius pratensis (Karg 1965). One genus and three species are reported from Slovakia for the first time: Alliphis kargi Arutunian 1991, Rafaphis with Rafaphis microsternalis Skorupski & Błaszak 1997, and Uroiphis greeni (Evans 1980). Alliphis and Uroiphis are represented in Slovakia by several species each; all other genera in Slovakia are represented by single species. The external morphology and ecology of the European genera and Slovakian species are reviewed. Most of the species are coprophilous and associated with coprophilous insects; a complete list of their phoretic associations is given. The eviphidid species occurring in Slovakia can be classified into three general ecological groups and five subgroups: (A) edaphic detriticoles, with four species; (B) saprophilous detriticoles, with five species, subdivided into (B1) non-specialised coprophiles, with one species, and (B2) specialised coprophiles, with four species; (C) insecticoles, with nine species, subdivided into (C1) non-specialised insecticoles, with three species, and (C2) specialised insecticoles, with six species. Uroiphis montivagus sp. nov. is not classified ecologically because it is only known from two specimens. Some species that occur in very fresh wet dung or very humid habitats (Alloseius pratensis, Crassicheles striatus, Neocrassicheles sternomus sp. nov.), have a specific morphological adaptation consisting of elongate pointed lateral lobes on pulvilli II–IV in the non-phoretic female. An elongation of some components of the pulvillus also occurs in some strongly hygrophilous Blattisociidae, and the modified pulvillus appears to facilitate the mite’s movement in semiaquatic substrates.